DISAPPOINTMENT AND REGRETTING REPSENTATIONS IN DUNKIRK AND 1917 MOVIES - Dedi Sulaeman; Anisa Hanifah (CALL, 2022)
The aim of this research was to compare two movies that contain similar perceptions of psychological impact on war, disappointment and regret, from Dunkirk and 1917 movies. Disappointment and regretting arise between British soldiers in movies that were directed by Christopher Nolan and Sam Mendes, which coincidentally both of these films raised the setting in World War I and II. Therefore, this research uses literary criticism and comparative literature methods in examining Dunkirk (2017) and 1917 (2019), to produce both similarities and differences in the psychological and emotional impact on British soldiers. In addition, this research uses a descriptive method with a qualitative approach using Peirce’s sign semiotic analysis. The result of this research is that readers will be able to recognize the differences between the two movies from literary perspective and psychological review from the failures of war in Dunkirk (2017) and 1917 (2019). These two films ultimately interpret disappointment in almost the same way and regret in the form of the loss of a loved one. The behavior of people who experienced both psychological impacts also indicates similarities, sadness, annoyed, and angry. Keywords: disappointment, index, regretting, representations